Students’ mathematics learning attitudes and behaviors: A case study of boarding school alumni in higher education - Crismono, Prima Cristi; Siti Lailatul Maghfiroh; Harapandi Dahri; Mahnawawe Yakoh (Jurnal Elemen, 2025)
Islamic boarding school (pesantren) education emphasizes moral discipline, obedience, and religious devotion, shaping students’ character from an early age. However, when pesantren graduates enter university, particularly in subjects like mathematics that require analytical thinking and problem-solving, they often face adaptation challenges. While pesantren instills strong ethical values, it generally lacks learning strategies that develop higher-order cognitive skills. This study investigates how pesantren education influences university students’ learning attitudes and behaviors in mathematics courses, focusing on learning motivation, active engagement, and time management. The research uses a quantitative approach with a descriptive correlational design. The sample consists of 132 students from pesantren backgrounds enrolled at the Islamic University of Jember, selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through Pearson correlation, ANOVA, and linear regression. Findings reveal that pesantren education has only a limited effect on students’ academic attitudes in mathematics, especially in motivation and engagement. Although it supports character development, pesantren education does not sufficiently equip students with the analytical skills required for university-level learning. The study recommends integrating more analytical and interactive teaching methods into pesantren curricula to help students adapt and succeed academically.